Sosialisasi PP No. 38 Tahun 2011 untuk Meningkatkan Kesadaran Masyarakat akan Pentingnya Sumberdaya Sungai di Desa Sumber Brantas, Bumiaji, Batu - Umi Zakiyah; Andi Andi Kurniawan; Mulyanto Mulyanto; Supriatna Supriatna; Mohammad Mahmudi; Sri Surdayanti; Nanik Retno Buwono; Lutfi Ni’matus Salamah; Alivia Salsabila K.T.S; Riska Ayu Lestari (I-Com: Indonesian Community Journal, 2024)
River water quality is getting worse due to lack of public awareness about the importance of river water quality. Efforts that can be made to increase public awareness are through law enforcement. This is done to instill a basic foundation in preserving the environment, and refers to the implementation of Government Regulation Number. 38/2011 which regulates rivers. Awareness raising is done by socialization method to the community about the existence of the government regulation. The area used as a socialization study is the community of Sumber Brantas Village, Batu, which is located near the upstream of the Brantas River. Some of these communities are not aware of the existence of government regulations governing rivers. In addition, there is a laij problem, namely the existence of environmentally unfriendly waste. So to realize the environment around river resources, there needs to be cooperation between various parties, including the community, government, and industry players. Cooperation is carried out to build a foundation in implementing the applicable law. In addition, synergy is also needed in providing sustainable solutions to problems faced around the river area.